High Prevalence of USA300 Among Clinical Isolates of Methicillin-Resistant Staphylococcus aureus on St. Kitts and Nevis, West Indies - Guardabassi, Luca; Moodley, Arshnee; Williams, Andrea; Stegger, Marc; Damborg, Peter; Halliday-Simmonds, Iona; Butaye, Patrick (Frontiers in Microbiology, 2019)
Limited information is available on antimicrobial susceptibility and clonal distribution of Staphylococcus aureus in the Caribbean region. The aims of this study were to determine the prevalence of antimicrobial resistance among clinical S. aureus isolates and to reveal the frequency and population structure of methicillin-resistant S. aureus (MRSA) in St Kitts and Nevis, a small island country in the West Indies. A total of 152 S. aureus were collected from consecutive samples submitted to the clinical microbiology laboratory of the main referral hospital from March 2017 to January 2018. Samples came from all units in the hospital and a small number came from external submissions. All S. aureus isolates were confirmed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. MICs of clinically relevant antimicrobials were determined by broth microdilution, and diversity of MRSA isolates was assessed by whole genome sequencing (WGS) analysis. MRSA accounted for 45% (69/152) of the isolates. The highest rates of resistance to non-β-lactam agents were observed for erythromycin (55%), moxifloxacin (41%) and levofloxacin (40%), whereas resistance to the other drugs tested was ≤ 6%. All isolates were susceptible to ceftaroline, linezolide, teicoplanin, telavancin and vancomycin. WGS-based multilocus sequence typing (MLST) showed that approximately 88% of the MRSA isolates belonged to ST8. Single nucleotide polymorphism (SNP) analysis showed 923 SNPs between the MRSA ST8 isolates, indicating a large degree of genetic diversity within ST8 isolates. However, all ST8 strains clustered within the distinct clade that defines the USA300 North American Epidemic lineage (PVL+, ACME +, SCCmec IVa). Our data show high levels of methicillin, macrolide and fluoroquinolone resistance amongst clinical isolates of S. aureus on St Kitts and Nevis. The USA300 North American epidemic lineage is responsible for the vast majority of MRSA infections on this Caribbean island.